DEGRADATION OF BIOPLASTICS UNDER THE INFLUENCE OF SEVERAL ENVIRONMENTAL CONDITIONS (Pakistan Journal of Science, 2022)
The rising environmental risks that plastics bring led to the development of bioplastics from renewable biomass resources. Glycerol is used to starch to create high-quality bioplastics. Plastics are fundamentally synthetic or synthetic-like materials that do not disintegrate. This study aims to investigate the degradation of bioplastics. Synthetic plastics are more damaging to the environment than bioplastics. Soil, compost, and water are just a few of the environments where the bio-plastics can degrade. The bioplastic components are buried in composite soil or loam sand in order to weigh them and take photographs of the breakdown activity. Different weather circumstances, such as temperature, humidity, rainfall, sunshine intensity, and sunlight duration, were recorded in order to study the impact of weather on the degrading activities. The comparison of the results showed that hydrophilic enzymes were used to carry out the bio-plastics' breakdown activity. After saturation, the initial regenerative material absorbs soil moisture, increasing weight by up to 87%. Following the start of the degradation process, the weight of the bio-plastics gradually decreased. Microorganisms from the soil that invade help the deterioration process. Rainfall, humidity, and the amount of sunlight all have an impact on the environment and how quickly bioplastics degrade. The rate at which bio-plastics degraded increased as a result of the soil's increased microbial activity brought on by the increased solar intensity.
Keywords: Bioplastic; Degradability and Purified Glycerol